Brahms’ Stilwandel in der Klangkonstruktion der Streicherkammermusikwerke - Maruyama, Yoko (Die Musikforschung, 2022)
Without doubt the sound-color of a certain instrument or group of instruments is an essential musical component, yet its realization in compositions is rarely the subject of analytical studies. This paper explores Brahms’ treatment of Klangfarbe (sound-color or instrumental timbre) in his string chamber works and argues that it is strongly related to the musical structure and the development of Brahms’s compositional technique over time. In his early sextets, regrouping and repositioning of instrumental parts occurs mostly at structural turning points, causing a regular change of the sound. In contrast, his late quintets are characterized by more fluent, irregular changes of instrumental combinations. On one hand, this is a result of the flexible part-writing realized through sophisticated counterpoint and motivic development. On the other, it may reflect his mature imagination of sound-color cultivated through his musical activities and experience, as such flexible treatment of instrumental timbre supports the structural complexity.